GENRE OF ‘THIS ODD WORLD’ COLUMN in the Jakarta Post 2013 - Rahayu, Dewi Indah (LANTERN (Journal on English Language, Culture and Literature), 2014)
A newspaper is a printed publication of information about news, events, articles or editorials published daily or weekly. Usually in newspaper, we can find some columns with different contains and form of text or Genre. Genre is a type of text from language usage to get something in spoken or written (Gerot and Wignell, 1995: 17). The writer believes it is necessary to undertake an analysis of a column in a newspaper. To identify a genre, there are some theories which can be applied. They are Genre, Systemic Functional Grammar and Nominal Group by Gerot and Wignell.